The Rising of “Alblish” (Albanian + English)—Data Collection and Analysis of Anglicisms in the Albanian Language - Kapo, Irena (Frontiers in Communication, 2022)
This paper investigates the impact of English on the Albanian language, a language contact phenomenon hitherto largely unexamined by Albanian and non-Albanian linguists alike. This contact mainly started as an indirect one at the beginning of the twentieth century, primarily via translations, the establishment of several educational institutions with the support of American and British associations and Albanian immigration into English-speaking countries. Several newspapers introduced a considerable number of Anglicisms into Albanian during the first half of the twentieth century, a good quantity of which “survived” even during the communist years of isolation. Those Anglicisms which made their way into the Albanian language until the 1990s and which have established themselves in the Albanian of today are mainly from the domains of culture and sports. The fall of the communist regime exposed the Albanian language to external linguistic and social factors, bringing about a flood of Anglicisms in different lexical fields other than culture and sport, such as business, information technology, politics, and medicine. The current database of Anglicisms in Albanian used for the purpose of this Brief Research Report was collected in the framework of the GLAD (Global Anglicism Database Network) project, http://gladnetwork.org. It includes 1,895 Anglicisms from newspapers and dictionaries, all integrated in a single file. The report first provides background information regarding the growing impact of English on the Albanian language during the three time periods under review (early twentieth century until 1960, 1960 to 1990, and 1990 to the present day). This is followed by an account of the data and the methods applied in the research. Subsequently, the findings and results are presented and discussed from a morphological, lexical, and syntactical perspective. The final outcomes are then used as a basis for the identification of Albanian language structures or patterns the English borrowings have managed to penetrate as well as of the level of adaptation English borrowings have in Albanian.